2022
DOI: 10.1002/nau.24959
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial cystitis/bladder pain syndrome (IC/BPS): Single‐center 20 year experience and treatment results in India

Abstract: Interstitial cystitis/bladder pain syndrome (IC/BPS) is an enigmatic disease that is difficult to treat. Even among physicians, the prevalent belief is that patients do not improve over time. In this study, we retrospectively reviewed our experience and treatment results for patients diagnosed with IC/BPS at our clinic in India over the past 20 years. Materials and Methods: Three hundred and eighty IC/BPS patients diagnosed between January 2001 and December 2020 were included. Patients underwent cystoscopy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…VAS scores are also likely to differ for different treatment modalities, as inferred from a systematic review study which reported that VAS score improved in cyclosporine A group compared to pentosan polysulfate sodium group. 10,11 In our study, 11% and 42% patients who received oral therapy and tacrolimus, respectively, had "very severe pain" in VAS assessment at baseline, which reduced to 3% and 8%, respectively, at 3month follow-up.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…VAS scores are also likely to differ for different treatment modalities, as inferred from a systematic review study which reported that VAS score improved in cyclosporine A group compared to pentosan polysulfate sodium group. 10,11 In our study, 11% and 42% patients who received oral therapy and tacrolimus, respectively, had "very severe pain" in VAS assessment at baseline, which reduced to 3% and 8%, respectively, at 3month follow-up.…”
Section: Discussionmentioning
confidence: 53%
“…One of the studies has reported that in their evaluation ICSI was considerably decreased in the amitriptyline (MD: -4.9), cyclosporine A (MD: -7.9), and certolizumab pegol (MD: -3.6) groups compared to the placebo group. 10,11 Analysis of IUSS scores at baseline found that about two-third (61.8%; N=34) patients with IC/BPS experienced severe disease condition. At 3-month follow-up, about three quarters (76%; N=42) patients with IC/BPS experienced mild disease condition.…”
Section: Discussionmentioning
confidence: 99%
“…IC in humans and cats also appears to be a dimensional rather than a categorical condition; patients may have minimal, mild, moderate, or severe symptoms that can vary over time rather than simply being present or absent. This has been studied most commonly in women (63)(64)(65). IC is also dimensional in cats, and more commonly severe in males because they can develop urethral obstruction (66).…”
Section: Patient Presentationmentioning
confidence: 99%